2018
DOI: 10.5194/acp-2018-1193
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanism of ozone loss under enhanced water vapour conditions in the mid-latitude lower stratosphere in summer

Abstract: <p><strong>Abstract.</strong> Water vapour convectively injected into the mid-latitude lowermost stratosphere could affect stratospheric ozone. The associated potential ozone loss process requires low temperatures and an elevated water vapour mixing ratio. An increase in sulphate aerosol surface area due to a volcanic eruption or geoengineering could increase the likelihood of occurrence of this process. However, the chemical mechanism of this ozone loss process has no… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…The final scenario, that other processes are contributing to O 3 reduction in tropical environments, seems most likely. Previous studies have identified the possibility of chemical destruction of O 3 through chlorine activation when an airmass is cold and wet enough and contains a sufficient amount of inorganic chlorine, though the extent of possible destruction is still a subject of debate (Anderson et al., 2017, 2012; M. J. Schwartz et al., 2013; Robrecht et al., 2019; Schoeberl et al., 2020). At the level of maximum O 3 reduction observed in convectively influenced MLS layers within tropical environments, temperatures are less than 205 K ∼50% of the time and less than 200 K ∼10% of the time while H 2 O concentrations are typically ∼5–7 ppmv (Figures 4c and 6b).…”
Section: Discussion Of Ls O3 Impactsmentioning
confidence: 99%
See 1 more Smart Citation
“…The final scenario, that other processes are contributing to O 3 reduction in tropical environments, seems most likely. Previous studies have identified the possibility of chemical destruction of O 3 through chlorine activation when an airmass is cold and wet enough and contains a sufficient amount of inorganic chlorine, though the extent of possible destruction is still a subject of debate (Anderson et al., 2017, 2012; M. J. Schwartz et al., 2013; Robrecht et al., 2019; Schoeberl et al., 2020). At the level of maximum O 3 reduction observed in convectively influenced MLS layers within tropical environments, temperatures are less than 205 K ∼50% of the time and less than 200 K ∼10% of the time while H 2 O concentrations are typically ∼5–7 ppmv (Figures 4c and 6b).…”
Section: Discussion Of Ls O3 Impactsmentioning
confidence: 99%
“…However, some proportion of the decreased O 3 concentrations can likely be attributed to dilution by tropospheric air. The extent to which chemical destruction of O 3 occurs is still largely unknown and is a topic of debate within the community (e.g., Robrecht et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Using global Version 3 observations from the Aura Microwave Limb Sounder (MLS) over the years 2005–2012, Schwartz et al (2013) (“S2013” hereinafter) revealed that OCEs over the North American monsoon area (“NA”) yield elevated H 2 O in the LMS in up to 1% of profiles. While numerous studies discuss localized negative correlations between OCEs and ozone concentrations (e.g., Anderson et al, 2012; Héron et al, 2020; Solomon et al, 2005), the overall impact of OCEs on stratospheric ozone is currently believed to be low (e.g., Homeyer et al, 2014; Robrecht et al, 2019; Schwartz et al, 2013; World Meteorological Organisation, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Robrecht et al (2019) has revisited the SEAC 4 RS data and used the CLAMS model to explore the possibility of chemical ozone loss following the convective injection of water vapor into the lower stratosphere. With a series of model experiments, they found that the injected water vapor amount had to exceed 10 ppmv, and there had to be sufficient aerosol nuclei and high amounts of reservoir chlorine (~1 ppbv of Cl y ) to produce~60% ozone loss.…”
Section: Introductionmentioning
confidence: 99%
“…With a series of model experiments, they found that the injected water vapor amount had to exceed 10 ppmv, and there had to be sufficient aerosol nuclei and high amounts of reservoir chlorine (~1 ppbv of Cl y ) to produce~60% ozone loss. They found that under normal summer midlatitude conditions, Cl y is believed to be~0.15 ppbv (based on observed correlation with CH 4 ) and with a 20 ppmv injection of water, Robrecht et al (2019) computed an ozone loss of only~9%. According to MLS observations compiled by Schwartz et al (2013) convectively injected water levels exceeding 20 ppmv are rarely observed at 16 km (~100 hPa) and higher altitudes.…”
Section: Introductionmentioning
confidence: 99%